Optimizing scaffold pore size for tissue engineering: insights across various tissue types - Mukasheva, Fariza; Adilova, Laura; Dyussenbinov, Aibek; Yernaimanova, Bota; Abilev, Madi; Akilbekova, Dana (Frontiers in Bioengineering and Biotechnology, 2024)
Scaffold porosity is a critical factor in replicating the complex in vivo microenvironment, directly influencing cellular interactions, migration, nutrient transfer, vascularization, and the formation of functional tissues. For optimal tissue formation, scaffold design must account for various parameters, including material composition, morphology, mechanical properties, and cellular compatibility. This review highlights the importance of interconnected porosity and pore size, emphasizing their impact on cellular behavior and tissue formation across several tissue engineering domains, such as skin, bone, cardiovascular, and lung tissues. Specific pore size ranges enhance scaffold functionality for different tissues: small pores (~1-2 µm) aid epidermal cell attachment in skin regeneration, moderate pores (~2-12 µm) support dermal migration, and larger pores (~40-100 µm) facilitate vascular structures. For bone tissue engineering, multi-layered scaffolds with smaller pores (50-100 µm) foster cell attachment, while larger pores (200-400 µm) enhance nutrient diffusion and angiogenesis. Cardiovascular and lung tissues benefit from moderate pore sizes (~25-60 µm) to balance cell integration and nutrient diffusion. By addressing critical design challenges and optimizing pore size distributions, this review provides insights into scaffold innovations, ultimately advancing tissue regeneration strategies.